Utility of Risk of Malignancy Index Four (RMI- 4) in Prediction of Oncological Outcomes in Adnexal Masses: A Retrospective Analysis - Ramani Gangadharan Ashitha; AdarshDharmarajan; Sanjay Badesara (International Journal of Pharma and Bio Sciences, 2024)
Adnexal masses are commonly detected during imaging studies and are a common indication for exploratory surgery. Accurate assessment of adnexal mass helps to triage patients and prompt referral. Extensive surgery should be performed in an oncology centre as surgical staging is a critical prognostic parameter in ovarian malignancy. The main objective of this study was to assess the utility of the risk of malignancy index four (RMI-4) in predicting malignancy in ovarian mass. Retrospective study of adnexal mass patients who underwent primary surgery. RMI 4 was determined. Response operating curve (ROC) was used to analyse the usefulness of the RMI4 score in predicting benign from malignant lesions. A total of 117 patients with adnexal masses, of which, based on pathology reports, 101 patients (86.3%) had malignancies, 11 patients (9.4%) were benign, and 5 patients (4.3%) were borderline. Serous cystadenocarcinoma (n=76) was the most common malignant lesion. The serum concentration of CA125 in benign neoplasms was 28.5 with a range of 4 to 290 U/mL, while in malignant tumours, the CA 125 was 239.8 (3.4 to 11750) U/mL. The mean RMI 4 value in malignant lesions was 14896, ranging from 870 to 752000. The RMI 4 had a sensitivity of 94% and a specificity of 62.5%. The positive predictive value of RMI4 is 94.1%, and the negative predictive value is 62.5%, with an accuracy of 89.74%. RMI 4 can be a useful tool for the initial assessment of patients with pelvic masses, and women with adnexal masses can be referred promptly to gynaecologic oncologists for early management.